Analisa Kompresi File Teks Dengan Kombinasi Metode Burrows-Wheeler Transform Dan Shannon-Fano - Boy Alfredo Silaban (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
With the development of computer technology today it can be used for various things, one of which is storing files. The larger the size of the file stored on the computer, the greater the storage space. The greater the storage space required, the greater the costs incurred. In addition, files that have a large size can cause problems when transmitting files. Therefore, methods emerged that aimed to compress files in order to save storage space for these files, one of which was compression. With compression, it is hoped that it can save costs and time spent in order to add file storage media facilities on a computer and speed up the file transfer process. After carrying out the compression process of the Shannon-Fano and BWT algorithms, it can be concluded that the combination of the BWT algorithm and the Shannon-Fano algorithm is more capable of reducing the size capacity in compressed pdf text files, because the compression process using the combination of the BWT algorithm and the Shannon-Fano algorithm is able to reduce the size data from the initial value. The combination of the BWT Algorithm and the Shannon-Fano Algorithm is able to compress pdf text files more efficiently than compression applications from the widely circulated online web.